Women's Obi Belt Design With Bolon Traditional House Element Embellishments - Selah Asih Widiastuti; Mudjiati (Journal of Creative Industries and Vocational Innovation, 2025)
Indonesia is an archipelago with 34 largest provinces, one of which is North Sumatra. The Batak tribe comes from North Sumatra. The wealth of the Batak tribe in culture is one of the traditional houses, namely ornaments. The Toba Batak Traditional House is one of the legacies of the Batak ethnic tradition which until now still leaves many philosophical and beautiful values. Likewise, the elements attached to the traditional house building are often called gorga. The purpose of the design is to develop the motif of the Bolon traditional house elements, as well as to find out the results of applying the motif of the Bolon traditional house elements to the design work of women's fashion accessory products so as to create a beautiful, modern and meaningful motif renewal. The process of applying the motif of the Bolon traditional house elements is the development of the motif by making an initial design such as a sketch of the shape from the original reference of the gorga ornament then stylizing the elements one by one before being designed to lengthen following the product pattern. The technique used to realize the product is using the digital printing technique. Using 20s Cotton Twill fabric as the main material. The colors applied to the design motifs of the elements of the Bolon house each have a meaning that is interrelated with the philosophy of each element of the Gorga of the Bolon house.